Analisis Pengaruh Kinerja Keuangan Terhadap Return Saham Perusahaan Transportasi Dan Logistik Di BEI Tahun 2020-2022 - Maqbula Arochman (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
The aim of this research to examine the influence of Earning Per Share (EPS), Price Book Value (PBV) and Debt To Equity Ratio (DER) on Stock Return. The research was conducted on Transportation and Logistic Companies on the Indonesia Stock Exchange in 2020-2022 using a yearly period. The sample use in the research totaled 17 Transportation and Logistic Companies listed on the Indonesia Stock Exchange during the 2020-2022, so that the data obtained was 51 observations. The sample selection was carried out using purposive sampling methode. The analitical technique used in the research is multiple regression, while testing the hypothesis using the t-test with a significance level of 5%. The result of data processing show that Earning Per Share (EPS)has a significant effect on Stock Return. Meanwhile, Price Book Value (PBV) and Debt To Equity Ratio (DER) bave no significant effect on Stock Return.